Etika Komunikasi Digital Dalam Media Sosial Siswa di MTS Darul Arifin Pantai Cermin - Atika Hanan Julia Harahap; Nurhalimah Harahap (Universitas Garut, 2026)
This study aims to analyze students' digital communication ethics, factors influencing communication behavior, and the role of schools in fostering and improving digital communication ethics in social media use. This study used a qualitative approach with observation, interviews, and documentation methods. The research subjects consisted of teachers and students. The results indicate that most students have a fairly good understanding of the importance of using polite language, respecting others, and being responsible in online interactions. Internal factors, such as personality, self-control, and an understanding of digital ethics, as well as external factors, such as family, school, and peer environments, influence students' communication behavior on social media. Schools play an active role through character education, digital literacy, teacher role models, and collaboration with parents. However, some students are still inconsistent in implementing digital communication ethics, requiring ongoing guidance. This research is expected to serve as evaluation material and a reference for improving the quality of digital communication ethics guidance in educational environments